2012
DOI: 10.1371/journal.pone.0042526
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domains of TNF-Related Apoptosis-Inducing Ligand (TRAIL) Receptors 1 and 2 Co-Regulate Apoptotic Signaling Capacity

Abstract: TNF-related apoptosis-inducing ligand (TRAIL) is a member of the tumor necrosis factor (TNF) ligand family that exerts its apoptotic activity in human cells by binding to two transmembrane receptors, TRAILR1 and TRAILR2. In cells co-expressing both receptors the particular contribution of either protein to the overall cellular response is not well defined. Here we have investigated whether differences in the signaling capacities of TRAILR1 and TRAILR2 can be attributed to certain functional molecular subdomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…The extracellular domain of these receptors contains two complete CRDs, which are important for ligand binding. A recent report suggested a co-regulatory role for the transmembrane domain of TRAIL-R1 and TRAIL-R2 for the apoptotic signalling capacity [67]. The intracellular part of TRAIL-R1 and TRAIL-R2 harbours a full length death domain.…”
Section: Structure Physiology and Pathophysiology Of Tnfr1 Trailmentioning
confidence: 99%
“…The extracellular domain of these receptors contains two complete CRDs, which are important for ligand binding. A recent report suggested a co-regulatory role for the transmembrane domain of TRAIL-R1 and TRAIL-R2 for the apoptotic signalling capacity [67]. The intracellular part of TRAIL-R1 and TRAIL-R2 harbours a full length death domain.…”
Section: Structure Physiology and Pathophysiology Of Tnfr1 Trailmentioning
confidence: 99%
“…In contrast, the intrinsic pathway is initiated through the release of signal factors by mitochondria within the cell, which is triggered by many cellular abnormal events [Fulda and Debatin, 2006]. Previous studies showed that TNF-alpha can bind to two different receptors TNFR1 or p55 and TNFR2 or p75 [Kruglov et al, 2008;Neumann et al, 2012]. It has been reported that TNF-alpha binding to TNFR1 is a known activator of pro-apoptotic signals in osteoblasts [Bu et al, 2003].…”
mentioning
confidence: 99%
“…Furthermore, Neumann et al . showed that the signaling capabilities of the death receptors DR4 and DR5 do not only depend on binding of TRAIL but the transmembrane domains together with their adjacent stalk regions also control the signaling strength. Likewise, the transmembrane domain and adjacent extracellular stalk regions of RANK could play a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…In a molecular dynamics study on binding between TNF-ligand family member TRAIL and its death receptor DR5, Wassenaar et al [33] proposed that through binding to TRAIL the conformational freedom of extracellular binding domains of DR5 was strongly restricted; this might also influence the stability of the intracellular death complex. Furthermore, Neumann et al [34] showed that the signaling capabilities of the death receptors DR4 and DR5 do not only depend on binding of TRAIL but the transmembrane domains together with their adjacent stalk regions also control the signaling strength. Likewise, the transmembrane domain and adjacent extracellular stalk regions of RANK could play a similar role.…”
Section: Discussionmentioning
confidence: 99%